Effects of shade location and protection from direct solar radiation on the behavior of Holstein cows - Oliveira, Steffan Edward Octávio [UNESP]; de Melo Costa, Cíntia Carol [UNESP]; Chiquitelli Neto, Marcos [UNESP]; Dalla Costa, Filipe Antônio [UNESP]; Maia, Alex Sandro Campos [UNESP] (Springer Nature, 2019)
Two trials (E1 and E2) were performed to assess the behavior of eight Holstein dairy cows with 367 ± 58 kg of body weight and 10.52 ± 0.08 kg of milk yield. A 4 × 4 Latin square design (four periods of lactation and four levels of solar blockage) with four paddocks was used. Each paddock contained a wood shading structure covered with a cloth that blocked 30% (T1), 50% (T2), 70% (T3), or 100% (T4) of direct solar radiation. In the first trial (E1) each shade structure was located approximately 40 m from the feeder and water troughs; in the second trial (E2), the distance was reduced to 5 m. Air temperature (TA, °C), relative humidity (RH, %), wind speed (U, ms−1), black globe temperature (TG, K), mean radiant temperature (TMR, K), radiant heat load (RHL, W m−2), and local shortwave radiation (RS, W m−2) were recorded at 15-min intervals from 08:00 to 17:00 h. Four behavioral activities were recorded: grazing, eating at the feed trough, ruminating, and idling. For each of these activities, animal posture (lying or upright) and location (under shade or exposed to sunlight) were recorded. The meteorological conditions showed similar variations from 8:00 to 17:00 h between the two trials. However, the air temperatures in E1 were lower (± 2 °C) than those in E2. In a PCA analysis, the first and the second principal components explained 56.87% and 21.85%, respectively, of the total variation in the behavioral variables. Under the E1 conditions, the animals did not seek shade, whereas in E2, the dairy cows spent 35 ± 5% of their time lying and idling in the shade. At a solar radiation blockage of 100%, cows were in the shade more than 60% of the time due to the intensity of solar radiation, which was 722.19 ± 14.59 W m−2 at 11:45. In a PCA analysis, the first and the second principal components explained 65.18 and 22.3%, respectively, and 87.48% together, of the total variation in the original variables. Consequently, it was possible to develop a shade index (IST) based on the first two components. In E1, animals spent very little time in the shade, spending only 0.15% of total time under the shade, irrespective of blockage. However, E2 cows used shade, reaching almost 80% of time under the shade, at midday, when the blockage was 100%.
Keywords: Cow comfort; Heat stress; Shade use; Solar irradiance; Tropical condition